Reviewing Footrot in Sheep - Caetano, P (2018)
Ovine footrot is the main cause of lameness in sheep around the world and is responsible for extensive economic and welfare impacts. It can be an extremely contagious disease, resulting from the invasion of the interdigital tissue by a complex mixture of bacteria, in which Dichelobacter nodosus is a required component. Strains of D. nodosus can be benign or virulent, but they are not always related with the clinical expression of footrot, complicating the diagnostic process. Several efforts have been made over recent decades to control the disease, but it remains endemic in the major sheep-raising countries of the world. The use of more efficient therapeutic procedures and better farm management practices or the development of new selective breeding tools and strategic vaccination protocols are some of the key measures that may improve footrot control in the future.